FAKTOR PEMINATAN MATA KULIAH KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA MAHASISWA - Nur Bayti (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
Research with the theme "Factors of Specialization in Entrepreneurship and Family Environment Courses on Student Entrepreneurial Interest" has the aim of seeing whether the factors of entrepreneurial students arise from entrepreneurship courses or entrepreneurial specialization arises from the family environment. The method used in this study is through a literature study where the method used is to collect library data, read and record and collect some previous research to answer the research. The study turned out to suggest that the provision of entrepreneurship courses to students had a real and positive effect on students’ entrepreneurial interests. Family environment factors such as entrepreneurial encouragement have a fairly good effect on students’ entrepreneurial interests